2019
DOI: 10.14802/jmd.18048
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Hearing Impairment Frequently Occurs in Early-Onset Parkinson’s Disease

Abstract: Objective Recent reports of hearing impairment in Parkinson’s disease (PD) have suggested that auditory dysfunction could be a non-motor manifestation of PD. These reports were based on observations of elderly patients for whom presbycusis may, to some extent, have contributed to hearing dysfunction. Therefore, we aimed to explore the auditory functions in younger patients with PD. Methods We conducted a case-control study in a relatively younger (< 55 years of age at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
1
27
2
2
Order By: Relevance
“…The difference in audiometric thresholds between patients with Parkinson's disease and controls, by means of PTA testing, is in agreement with previous clinical results ( Vitale et al , 2012 , 2016 ; Shetty et al , 2019 , Scarpa et al , 2020 ). Our results extend previous observations by tackling a large cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difference in audiometric thresholds between patients with Parkinson's disease and controls, by means of PTA testing, is in agreement with previous clinical results ( Vitale et al , 2012 , 2016 ; Shetty et al , 2019 , Scarpa et al , 2020 ). Our results extend previous observations by tackling a large cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
“…In the field of hearing research, alterations in patients with Parkinson's disease were observed in different frequency ranges, although the association with disease features has not been fully defined ( Gawel et al , 1981 ; Fradis et al , 1988 ; Vitale et al , 2012 ; Pisani et al , 2015 ; Folmer et al , 2017 ; Shetty et al , 2019 ). Recent studies have also demonstrated impairment in central auditory processing ( Folmer et al , 2017 ) and reduction of distortion-product otoacoustic emission (DPOAE) levels ( Pisani et al , 2015 ), which reflect cochlear outer hair cell function.…”
Section: Introductionmentioning
confidence: 99%
“…These studies did not find significant differences between patients with PD and HCs regarding pure-tone hearing thresholds. On the other hand, higher pure-tone hearing thresholds in patients with PD have been reported by other research groups in the middle to high frequency range (1.5-8 kHz) (21)(22)(23)(24)(25)(26)(27)(28). The differences between study results may be influenced by the approach chosen to analyze the data (e.g., categorical vs. continuous data-analysis, consideration of confounding variables, correction for multiple comparisons).…”
Section: Audiological Measurements Peripheral Auditory Testsmentioning
confidence: 90%
“…Each wave, labeled using Roman numerals, reflects the synchronous firing of different auditory cell populations. As such, waves I and II are derived from the distal and proximal regions of the (25,27,79,80). On the other hand, multiple other studies have reported prolonged latencies for the centrally generated waves III to V in patients with PD compared to age-matched HCs (21,24,28,(81)(82)(83)(84).…”
Section: Electrophysiological Measurements Short Latency Auditory Evomentioning
confidence: 98%
See 1 more Smart Citation